Investigating the Generation of Biophotons Induced by Low-Dose Beta-Irradiation and their Role in the Radiation-Induced Bystander Effect - Le, Michelle (My University, 2018)
The communication of information between irradiated and non-irradiated bystander cell populations and the subsequent expression of radiation-like responses in the non-irradiated population, formally referred to as the radiation-induced bystander effect, is a very well established phenomenon in the study of radiobiology. Intercellular communication of bystander signals is known to occur via the exchange of soluble factors through biological fluids and via the transfer of molecules between adjacent cells via gap-junctions. Both of these communication methods require some degree of physical contact between biological entities. However, observations made in the literature demonstrating the induction of radiation effects in optically-coupled, yet chemically-separated organisms raises the hypothesis that alternative radiation bystander communication mechanisms may exist that have not yet been explored. Following the detection of significant photon emission from human keratinocyte cells exposed to ionizing beta-radiation by Ahmad in 2013, the involvement of an electromagnetic bystander signal was proposed. While not yet established in the field of radiobiology, intercellular communication via electromagnetic signalling is widely studied in the field of biophotonics. The emission of electromagnetic radiation from biological material, called biophoton emission, and the subsequent communication of effects using those signals has been characterized both spontaneously and as a result of perturbation by various stressors. This thesis therefore aimed to investigate intercellular communication via electromagnetic signalling stimulated by low-dose ionizing radiation to identify a possible convergence between the fields of biophoton communication and radiation-induced bystander effects. The characterization of biophoton emission from human cell cultures was accomplished using a single photon counting photomultiplier tube. The results revealed that biophoton emission is exacerbated by external stimulation (beta-radiation), it possesses a dependence upon the activity of radiation delivered, the density of the irradiated cell culture, and cell viability. These results suggest that biophoton emission is governed by physical transitions between excited and ground states and may further be modulated by metabolic processes. An effect of beta-radiation-induced biophoton emission upon non-irradiated bystander cells was identified and manifested as a reduction in cell survival. The modulatory effects observed following the application of photomodulating agents to the bystander cultures support ultraviolet electromagnetic radiation as a responsible factor in the communication of bystander signals. Observation of photon emission across the entire ultraviolet, visible and infrared spectra lead to the suggestion that ultraviolet wavelengths are only a portion of the signal responsible for eliciting bystander responses and that coherent interaction of multiple wavelengths is probable in the intercellular exchange of information. The possibility of a link between biophoton bystander signalling and soluble factor mediated bystander effects was investigated next by isolating exosomes from biophoton-exposed bystander cultures. Positive bystander responses were exhibited by secondary reporter cells incubated with the exosomes isolated from the biophoton-exposed bystander cultures, thereby suggesting that biophoton signalling is a possible form of biological redundancy where it acts as an intermediary to trigger soluble factor release and further reinforce intercellular communication. Finally, the effect of beta-radiation-induced biophoton signals upon mitochondrial activity was assessed and revealed the capacity for biophotons to downregulate Complex I and ATP synthase activity. The demonstrated effect of biophotons upon mitochondria elucidates a candidate mechanism worthy of further exploration to determine how biophotons may trigger responses in bystander cells. Overall, this thesis elucidates an additional mechanism for intercellular communication between biological systems perturbed by low doses of ionizing radiation, in the form of an electromagnetic signal. This work contributes to the current perspective on biophoton bystander signalling as a potential source of biological redundancy, facilitating a means of intercellular communication when optical coupling but not chemical contact is available in a given system.
Keywords: Biophoton; Radiation; Ionizing; Beta; Bystander Effect; Radiation-Induced Bystander Effect; Ionizing Radiation; Cell Signalling